(untitled) (REMUNOM, 2023)
This study addresses the theme of psychology in the process of inclusive education for children with Autism Spectrum Disorder (ASD). Explains about this disorder, as well as about inclusive education, and aspects related to the psychologist’s role in the context of inclusion. The study was conducted through a literature review with the overall objective of understanding the psychologist’s role in the process of inclusive education for children with Level 1 ASD. The specific objectives were: discussing Disorder based on a literature review, describing the role of the school psychologist, and identifying the possibilities of intervention by this professional in inclusive education. The research findings highlight the importance of the psychologist in achieving inclusive education through actions that promote well-being, reduce fear, anxiety, and frustration, and integrate the four dimensions of intervention described in this study: macrosocial interventions and institutional, among school actors and targeted at the individual. It can be concluded that the psychologist’s involvement in the process of inclusive education for children with Level 1 ASD occurs in different ways, contributing not only to children with ASD but also benefiting all individuals involved in the teaching and learning process.